Phosphate Suppression of Arbuscular Mycorrhizal Symbiosis Involves Gibberellic Acid Signaling. (28th June 2021) - Nouri, Eva; Surve, Rohini; Bapaume, Laure; Stumpe, Michael; Chen, Min; Zhang, Yunmeng; Ruyter-Spira, Carolien; Bouwmeester, Harro; Glauser, Gaëtan; Bruisson, Sébastien; Reinhardt, Didier
Abstract: Most land plants entertain a mutualistic symbiosis known as arbuscular mycorrhiza with fungi (Glomeromycota) that provide them with essential mineral nutrients, in particular phosphate (Pi ), and protect them from biotic and abiotic stress. Arbuscular mycorrhizal (AM) symbiosis increases plant productivity and biodiversity and is therefore relevant for both natural plant communities and crop production. However, AM fungal populations suffer from intense farming practices in agricultural soils, in particular Pi fertilization. The dilemma between natural fertilization from AM symbiosis and chemical fertilization has raised major concern and emphasizes the need to better understand the mechanisms by which Pi suppresses AM symbiosis. Here, we test the hypothesis that Pi may interfere with AM symbiosis via the phytohormone gibberellic acid (GA) in the Solanaceous model systems Petunia hybrida and Nicotiana tabacum . Indeed, we find that GA is inhibitory to AM symbiosis and that Pi may cause GA levels to increase in mycorrhizal roots. Consistent with a role of endogenous GA as an inhibitor of AM development, GA-defective N. tabacum lines expressing a GA-metabolizing enzyme (GA methyltransferase—GAMT) are colonized more quickly by the AM fungus Rhizoglomus irregulare, and exogenous Pi is less effective in inhibiting AM colonization in these lines. Systematic gene expression analysis of GA-related genes reveals a complex picture, in which GA degradation by GA2 oxidase plays a prominent role. These findings reveal potential targets for crop breeding that could reduce Pi suppression of AM symbiosis, thereby reconciling the advantages of Pi fertilization with the diverse benefits of AM symbiosis.